A percepção dos gestores do Instituto Federal de Sergipe – IFs campus lagarto acerca das licitações sustentáveis - Santos, Fladson Ricardo Mendes dos (2017)
The need for nations to promote the growth of their economies without destroying the environment or sacrificing the well-being of future generations, transforming especially the business world, has become a challenge today. In view of it is fundamental relevance, sustainability has become more and more space in the various discussions, and in recent times the focus has been on the Public Administration, most probably for its state power, with a constitutional duty to implement public policies that collaborate with the economy. In the use of natural resources, ensuring their preservation and contributing effectively to the possibility of providing these resources for the future generations. The present study aims to diagnose the perception of the managers of the Instituto Federal de Sergipe (IFS) – Campus Lagarto, about the Sustainable Biddings. Methodologically, the study is classified as a field research, as the qualitative-descriptive approach, using a structured questionnaire for data collection, for treatment of clusters technique, allied to an index called Degree of Vision About Sustainable Biddings (GVLS). The results point to the fact that managers are sensitized about the possibility of behavioral changes, be they of a functional or institutional nature, for the adoption of Sustainable Biddings. Thus IFS – Campus Lagarto is suggested to implement Sustainable Biddings, using the Regulation and Standardization of Tender Procedures, Formatting a Sustainable Biddings Plan, Creating Environmental Education Programs for Managers and Periodic Surveys of Environmental Perception, Covering the Internal and External Community and Strengthening Internal Communication about Current Procedures and Standards.